O ritmo climático no Trópico de Capricórnio e a produção de uva : o estudo de caso "Marialva - PR" - Hiera, Mitchel Druz (2011)
This study verifies that the climatic conditions are favorable for Marialva good grape production. Since the 1960s, the City of Marialva, located in subtropical area, has its economy based on viticulture. This, in turn, is a culture that adapts best to the Temperate. Despite the geographical position of Marialva be inserted in the subtropical zone, the region's climate is characterized as a transition between the Tropical and Subtropical, bearing characteristic features of the two climates. For this research we used the four main elements of climate that influence the development of grapevine: temperature, precipitation, relative humidity and sunshine. As the climate of the study area favors the holding of two annual crops, this study included the two annual harvests, and the first annual harvest, held in the second half of the year was divided into two, according to the time of pruning performed by the producer. Results are shown as follows: first, the water requirements are presented, thermal, humidity and sunshine for each of the phenological stages of the vine, then, is demonstrated through a series of climatological 30 years, as each of the elements of the climate behaved in the periods studied the phenological stages of grapevine, and finally, after choosing the 2008/2009 season as high productivity, we performed the analysis of weather elements on a daily, for the months of season, trying to compare with the yield obtained. Climatic data were obtained from the climatological station of Maringa, associated with the National Institute of Meteorology. Points as main results: a) the pace of climate the second half, when it held its first annual harvest is more favorable to the exigencies of the vine, with lower temperatures at the beginning of the reproductive cycle and heavy rainfall at the end of this cycle, b) the pace of climate the first half, when it is held the second annual crop, is unfavorable to the requirements of the vine, but can not compromise productivity. Concluded that the climatic conditions of Northern Paraná may cause a fall in productivity, however, enables the development of two annual crops with crops in periods when there are shortages of the product on the market.